Double left atrial appendage: A diagnostic dilemma - Nilanjan Dutta; Debasis Das; Unmesh Chakraborty; Shubhadeep Das; Manish Kumar Sharma; Shivani Gajpal; Amitabha Chattopadhyay; Sanjiban Ghosh; Jayita Nandy Das (Wolters Kluwer Medknow Publications, 2023)
We report a unique intraoperative finding of an additional double left atrial appendage (LAA) during an arterial switch operation with ventricular septal defect closure in a 4-month-old girl. Immediately after the procedure, a prolapsing mass within the left atrium (LA) on the transesophageal echocardiogram raised concerns of a possible thrombus. The LAA was clearly visible with a pressure monitoring line which was put intraoperatively. To investigate further, cardiopulmonary bypass was resumed, and the heart was arrested and explored. There was an appendage-like structure, separate from the one that had the pressure monitoring line, which was inverted inside. It was pulled out from outside clearly establishing a double LAA. This report illustrates an example of a diagnostic dilemma caused by a double atrial appendage which was invaginated into LA masquerading as a mass or thrombus.